Supply and Demand for Child Care Services in Turkey : A Mixed Methods Study - World Bank (Washington, DC, 2015)
Despite increases in availability of center based child care and preschool services in Turkey over the last decade, both the supply of services and utilization remain low. There are regional disparities in availability and the majority of children and households remain unserved in terms of child care and preschool services. This report has collected and assessed information on the supply and demand for child care services in Turkey with the objective of identifying key constraints and opportunities to expand quality and affordable access. The analysis in this report shows that current utilization of child care services cannot be construed as lack of demand for services, but rather as a lack of demand for services at existing cost and price-quality structures. Existing services that respond to the needs of working mothers are mainly private services and tend to be more expensively priced than the willingness and ability to pay of the average household. For most women the difference between earnings and the cost of care is too low to justify joining the labor force and their willingness to pay for care does not cover the current median prices for child care and kindergarten services.